2019
DOI: 10.2217/pmt-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Case Series on the Use of Peripheral Nerve Stimulation for Focal Mononeuropathy Treatment

Abstract: Aim: This case series looks at outcomes in 39 patients implanted using the Bioness Stimrouter system on various isolated mononeuropathies. Patients & methods: A case series of 39 patients with a total of 42 implants were enrolled starting August 2017 at various pain management centers. Results: Of 39 patients studied, 78% of the participants noticed an improvement in their pain. There was a 71% reduction in pain scores with the average preprocedure score of 8 improving to 2 post-implant. Participants noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…There were no RCTs found that assessed the efficacy of PNS therapy to the suprascapular nerve in chronic refractory shoulder pain patients. Table 4 lists all four clinical reports obtained for stimulator implants on the suprascapular nerve [9][10][11][12]. Among the two case reports listed: one patient had no pain at rest and excellent shoulder joint range of motion at the 3-month follow-up [9], while the other had no pain and did not require any pain medications at 9 months post-implantation [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no RCTs found that assessed the efficacy of PNS therapy to the suprascapular nerve in chronic refractory shoulder pain patients. Table 4 lists all four clinical reports obtained for stimulator implants on the suprascapular nerve [9][10][11][12]. Among the two case reports listed: one patient had no pain at rest and excellent shoulder joint range of motion at the 3-month follow-up [9], while the other had no pain and did not require any pain medications at 9 months post-implantation [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the two case reports listed: one patient had no pain at rest and excellent shoulder joint range of motion at the 3-month follow-up [9], while the other had no pain and did not require any pain medications at 9 months post-implantation [11]. There was also a large prospective case series which included one patient who underwent an implant on the suprascapular nerve and experienced 66.7% improvement in pain scores and 80% improvement in movement capacity [12]. Lastly, there was a retrospective case series in which a subset of nine patients underwent suprascapular nerve stimulator implant: pain score improved > 50% for eight patients, mean pain improvement was 70%, and 6 patients had > 50% improvement at last follow-up which was between 2 to 4 years [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight RCTs and 11 observational studies considered for inclusion, three RCTs [ 95 , 134 , 136 ] and eight observational studies [ 66 , 98 , 103 , 104 , 113 , 116 , 121 , 142 ] were considered low quality on the appropriate ASIPP analysis and were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple new interventional pain management therapies have emerged over the past several years including, but not limited to, high frequency and burst spinal cord stimulation [4][5][6][7], dorsal root ganglion stimulation [8,9], cooled radiofrequency ablation [10,11], and temporary and permanent percutaneously implanted peripheral nerve stimulation (PNS) [12,13]. While the data in support of these therapies is growing at a rapid pace [14][15][16][17][18][19][20][21], insights into patient-preferences that may impact physician guidance and choice of treatment have not yet been characterized.…”
mentioning
confidence: 99%